EFEK LAJU PEMANASAN (HEATING RATE) TERHADAP DISTRIBUSI TEMPERATUR DAN KINERJA MODUL THERMOELECTRIC GENERATOR SP1848 SA - Nugroho Tri Atmoko; Haikal Haikal; Bagus Radiant Utomo; Fatimah Nur Hidayah; Emanuel Budi Raharjo (Jurnal Rekayasa Mesin, 2023)
Thermoelectric Generator (TEG) is an energy conversion technology that converts heat energy into electrical. There are several factors that affect the performance of TEG, one of which is the heat source. This research will investigate the use of waste heat by varying the heating rate on the performance of TEG in generating electricity and the temperature distribution profile through experimental studies on a laboratory scale. The heating plate is used to heat the hot surface of the TEG. There are three variations of the heating rate used, namely: Low (0.355°C/min), Middle (0.933 °C/min) and High (1.558 °C/min). Temperature measurements were carried out on the hot surface (Th), the cold surface (Tc) of the TEG module, and the ambient temperature (Ta) using Arduino temperature data logger. Meanwhile, to measure the electrical output in the form of voltage (V) generated by the TEG module, using the Arduino voltage data logger. The results show when the heating rate used is high (high heating rate) then the average electrical output of the TEG module produces a voltage of 5.34V. The heating rate on the hot surface of the TEG module will affect the difference in surface temperature and the performance of the TEG module in generating electricity.